Mechanical properties and dimensional stability of cement bonded particleboard from rice husk and sawdust - Sarkar, M; Asaduzzaman, M; Das, AK; Hannan, MO; Shams, MI (Bangladesh Journal of Scientific and Industrial Research, 2012)
This study was conducted to evaluate the properties of cement bonded particleboard made from rice husk and sawdust. Sawdust and rice husk fine boards were made using two ratios of cement and particles of 70:30 and 80:20, but rice husk coarse was made with a ratio of cement and particle of 80:20. The density of sawdust and rice husk fine boards in a ratio of cement and particles of 70:30 was 960 and 880 kg/m3 respectively. If the cement ratio was increased to the ratio of 80:20, the density increased to 1140 and 1200 kg/m3 respectively. The density of rice husk coarse boards was 980 kg/m3. The MOR of boards made from saw dust and rice husk fine in a ratio of 70:30 was 5.36 and 2.48 N/mm2 respectively. It was 5.30 and 4.63 N/mm2 in a ratio of 80:20. The MOE of saw dust and rice husk fine boards in a ratio of 70:30 was 3302.96 and 1684.52 N/mm2, and in a ratio of 80:20 it was 3569.28 and 3139.27 N/mm2 respectively. The MOR and MOE for rice husk coarse boards were 6.08 and 3041.71 N/mm2 respectively. Rice husk fine and rice husk coarse board showed excellent properties in a ratio of cement and particles of 80:20. Therefore, rice husk can be an alternative source of raw material for manufacturing of cement bonded particleboard. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13060 Bangladesh J. Sci. Ind. Res. 47(3), 273-278, 2012